Mobile agent location management in global networks - PATEL, R.B.; MASTORAKIS, Nikos E.; GARG, Kumkum (Annals of Spiru Haret University. Economic Series, 2010)
Mobility management is a necessity in highly dynamic and large-scale Mobile Agents (MAs) networks, especially in a multi-region environment in order to control and communicate with agents after launching. Existing mechanisms for locating MAs are not efficient as these do not consider the effect of location updates on migration time and produce network overload. This paper presents a hierarchical model for location management of MAs in global networks. Three protocols are developed, namely search, update and search-update. The location management technique uses one combination of search, update and search-update protocols throughout execution. Three cases are considered for Update and Search-Update Protocols. Thus, nine combinations of location management protocols are generated, from which an agent can dynamically select one as per requirement, to communicate with other agents on the global network. We have implemented these protocols on the system developed at IIT Roorkee, to evaluate the performance. Results indicate that overhead generated by these protocols does not affect the actual agent response and migration time[1].